Urinary Incontinence in Hospitalised Elderly Patients: Do Nurses Recognise and Manage the Problem? - Sabin Zürcher; Susi Saxer; René Schwendimann (Nursing Research and Practice)
This study examined to what extent nurses recognize urinary incontinence (UI) in elderly hospital patients, what UI interventions nurses realize, and if elderly inpatients are willing to raise the topic during their hospital stay. A convenience sample of 78 elderly inpatients in a Swiss hospital were screened for UI and asked if they were willing to be questioned about UI during hospitalisation. Nursing records were analysed as to whether UI had been recognized, and to collect data on interventions. Forty-one patients (51%) screened positive for UI, of whom 10 (24%) were identified as such in their nursing records. The single intervention documented was the use of incontinence pads. Only 5 patients preferred not to be asked about UI at hospital. Nurses in the study hospital should systematically ask elderly patients about UI and provide them with information on interventions.